2006
DOI: 10.1108/09556220610668473
|View full text |Cite
|
Sign up to set email alerts
|

Regional microclimate humidity of clothing during light work as a result of the interaction between local sweat production and ventilation

Abstract: Purpose -The aim of this study is to explore the influence of the clothing ventilation in three body regions on the humidity of the local clothing microclimates under five work-shirts immediately after the onset of sweating in light exercise. Design/methodology/approach -The clothing microclimate ventilations were measured at chest, back and upper arm using a manikin. Separate wear trials were performed to determine the sweat production and the humidity of the clothing microclimate at the same locations as whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
45
1
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 48 publications
(49 citation statements)
references
References 11 publications
(13 reference statements)
1
45
1
2
Order By: Relevance
“…This method has been shown to be repeatable and accurate, if the tracer gas is distributed equally over the microclimate regions. Efforts are under way to measure this ventilation for different regions of the body separately (Ueda et al, 2006).…”
Section: Direct Measurement Of Ventilationmentioning
confidence: 99%
“…This method has been shown to be repeatable and accurate, if the tracer gas is distributed equally over the microclimate regions. Efforts are under way to measure this ventilation for different regions of the body separately (Ueda et al, 2006).…”
Section: Direct Measurement Of Ventilationmentioning
confidence: 99%
“…The local VR of the experimental jackets were consistent with the previous studies of similar garments. 13,22 Significant effects of garment size (p<0.001), fabric permeability (p<0.001), wind speed (p<0.001), garment apertures (p<0.001) and locations (p<0.001) were observed according to ANOVA analysis. The larger of the p value, the more significant effect on the local VR.…”
Section: Resultsmentioning
confidence: 99%
“…10,13,14 However, neither of the studies considered the effects of wind and garment apertures and the combined effects of them on local VR. In addition, the garment local thermal properties have also attracted some attention.…”
Section: Ueda Et Al Compared the Local Vr Of 5 Diapers Between Diffementioning
confidence: 99%
“…In addition, Lotens and Havenith (1988) reported that a windproof jacket worn with an air space between it and the body induced considerable ventilation, the effects of which were indistinguishable from airpermeable clothing. Moreover, Ueda et al (2006) found that increased clothing ventilation soon after the onset of sweating had the advantage of keeping the wearer comfortable, by preventing an increase in skin moisture concentration. These results might explain the current observation that subjects felt less unpleasantly warm and more comfortable during exercise, and less humid both during exercise and recovery, when wearing DC rather than UDC clothing (See Figure 6).…”
Section: Discussionmentioning
confidence: 99%